Teaching as a Design Science : Building Pedagogical Patterns for Learning and Technology. - Laurillard, Diana (Taylor & Francis, 2012)
Teaching is changing. It is no longer simply about passing on knowledge to the next generation. Teachers in the twenty-first century, in all educational sectors, have to cope with an ever-changing cultural and technological environment. Teaching is now a design science. Like other design professionals -- architects, engineers, programmers -- teachers have to work out creative and evidence-based ways of improving what they do. Yet teaching is not treated as a design profession. Every day, teachers design and test new ways of teaching, using learning technology to help their students. Sadly, the.